Una Historia de las Indias entre África y América - Serge Gruzinski (Mélanges de la Casa de Velázquez)
Why not analyse Iberian expansion in Africa and Asia starting from the American continent? Here we look at how Las Casas conceived and described the links that were forged between Africa and America, with a threefold purpose: to explore the relationships between Portuguese and Castilian historians in the mid-16th century; to establish the extent to which African and American studies are still practically separate fields of research; and to examine the possibility and the necessary conditions for a global history.